Prenatal presentation of hereditary hemorrhagic telangiectasia – a report of two sibs. (9th August 2016) - Saleh, Maha; Miron, Ioana; Al‐Rukban, Hadeel; Chitayat, David; Nezarati, Marjan M.
Abstract : What's Already Known About This Topic? There are no publications linking prenatally detected hepatic arteriovenous malformations (AVM) with the diagnosis of hereditary hemorrhagic telangiectasia (HHT). To date only one case series reported symptomatic neonatal hepatic AVMs, none of which were detected prenatally. What Does This Study Add? We report two siblings with molecularly confirmed HHT who presented with symptomatic hepatic AVMs, one of which was detected prenatally. This report suggests that prenatal or neonatal hepatic AVMs merit evaluation for HHT.